The effect of pramipexole extended release on the levodopa equivalent daily dose in Lebanese Parkinson diseased patients - Faddoul L; Chahine B; Haydar S; Abourida S; Hallit S; Bou Raad E. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Objective: The objective of this study is to compute the potential benefit of Pramipexole ER on total levodopa equivalent dose (LED) and Unified Parkinson Disease Rating Score (UPDRS-III) compared to mono- or combined therapy of pramipexole IR and/or carbidopa/levodopa. Methods: This is a retrospective observational study conducted in a specialized PD (Parkinson Disease) and movement disease center in Lebanon between January and December 2017. Results: A total of 176 patient's record was reviewed. Pramipexole ER showed a significant difference on the mean changes in LED and UPDRS-III score. After 13 weeks of initiating Pramipexole ER, the mean decrease in LED was -49.42 mg for all patients (p < 0.001, CI 95% [35.28-63.55]) and the mean decrease in UPDRS-III score for all patients was -6 points (P< 0.001). According to the subgroup analysis, patients aged 65 years and below, the change in mean total LED from baseline ( 350.80 mg) was a decrease of 63.19 mg with a p<0.001, CI 95% [42.07-84.31]. In patients aged more than 65 years and shifted to mono or combined pramipexole ER therapy, the change in mean total LED from baseline (559.25 mg) was a decrease of 34.67 mg with a p<0.001 CI 95% [16.16-53.18]. In addition the results showed that in patients having an UPDRS-III score of less than or equal to 33, the change in mean total LED from baseline (436.73 mg) was a decrease of 56.76 mg (p<0.001; CI 95% [41.32-72.20]). However, in patients having an UPDRS-III score of more than 33 the change in mean total LED from baseline (545.06 mg) was a decrease of 2.96 mg with a p value < 0.844 CI 95% [27.32-33.15]. Conclusions: This study demonstrated the efficacy of Pramipexole ER on decreasing the total levodopa equivalent dose (LED).The role of health care professionals is to maintain the patient on the lowest effective levodopa equivalent daily dose and optimize the treatment therapy, thus decreasing the side effects that might arise from overdosing of antiparkinsonian drugs.